Why are hedonists less happy than eudaimonists? The chain mediating role of goal conflict and mixed emotions - Sun, Wujun; Liu, Lei; Jiang, Yuan; Fang, Ping; Ding, Xiaosheng; Wang, Guangjun (Frontiers in Psychology, 2023)
Human motivation for happiness involves two main orientations of hedonia and eudaimonia. Numerous studies have shown that hedonic motivation has a much smaller effect on happiness outcomes than eudaimonic motivation, but little is known about the reasons for this. According to the Self-Determination Theory and the Levels of Valence Model, this may be related to the different goal conflicts and mixed emotions elicited by the two motivations. To demonstrate this, the study examined the mediating effect of the above two variables between happiness motivation and life satisfaction. Furthermore, it explained why hedonists are less happy than eudaimonists by comparing the two happiness motivations in terms of their respective path effects. The study randomly selected 788 college students from 13 different provinces of China to examine the relationships between hedonic motivation, eudaimonic motivation, goal conflict, mixed emotions, and life satisfaction. The result showed that (1) the direct effect of hedonic motivation on life satisfaction was marginally significant, and the effect size was much smaller than that of eudaimonic motivation. (2) The direct and indirect effects of hedonic motivation were the opposite, with a large suppressing effect. In contrast, all paths of eudaimonic motivation positively affected life satisfaction. (3) Hedonic motivation negatively influenced life satisfaction through mixed emotions and the chain mediating effect of goal conflict and mixed emotions, whereas eudaimonic motivation positively influenced life satisfaction through these two mediating paths. （4）The effects on all paths of hedonic motivation were significantly smaller than those of eudaimonic motivation, except for the path mediated by goal conflict. This study explains why hedonists are less happy than eudaimonists from the perspective of goal pursuit, emphasizes the critical role of differences in goal pursuit state and experience between happiness motivation and life satisfaction, and provides new ideas for the study of the influence mechanism of happiness motivation. At the same time, the deficiencies of hedonic motivation and the advantages of eudaimonic motivation presented by the study provide directions for cultivating happiness motivation for adolescents in the practice field.